PENGARUH MANAJEMEN HUBUNGAN PELANGGAN TERHADAP KEPERCAYAAN DAN KOMITMEN PADA SALON NEW YORK 1 MATARAM - Nendy Pratama Agusfianto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study aims to (1) reveal the effect of customer relation management oncustomers’ commitments, (2) to find out the effect of customer relation management andcustomers’ trust, and (3) to uncover the effect of consumer trust on their commitment. Thistype of study belongs to associative research, which aims to investigate the relationshipbetween two or more variables. The population in this study encompassed all the customers ofNew York 1 beauty salon in Mataram. Using Malhotra opinion model, the number of samplesobtained was 65 people. The research data were collected through of use a questionnairedistributed to the a number of respondents, and the data analysis design employed for thepurpose was path analysis. Results of the analysis based on path analysis were presented asfollows (1) the management of customer relation management had no significant effect on thecustomers’ commitments, (2) the customer relation management had a significant and positiveimpact on the customers’ confidence, (3) the trust had a significant and positive effect on thecustomers’ commitment.Keywords : Customer Relation Management, Confidence, Commitment